2017
DOI: 10.1002/1878-0261.12080
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐to‐mesenchymal transition transcription factors in cancer‐associated fibroblasts

Abstract: Beyond inducing epithelial‐to‐mesenchymal transcription (EMT), transcriptional factors of the Snail, ZEB and Twist families (EMT‐TFs) control global plasticity programmes affecting cell stemness and fate. Literature addressing the reactivation of these factors in adult tumour cells is very extensive, as they enable cancer cell plasticity and fuel both tumour initiation and metastatic spread. Incipient data reveal that EMT‐TFs are also expressed in fibroblasts, providing these with additional properties. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 89 publications
2
44
0
1
Order By: Relevance
“…GSEA pathway analysis of Saa3-null CAFs revealed a significant enrichment in Proliferation and Angiogenesis hallmarks, as well as up-regulation of Sonic Hedgehog, TNFα/NFκB, and IL-6 pathways. Moreover, we observed enrichment in genes implicated in EMT, suggesting increased plasticity of Saa3-null CAFs as well as their potential effect in inducing an undifferentiated phenotype in their neighboring tumor cells (39). In addition, the Saa3-null CAFs displayed upregulation of the apical junction pathway, a property that predicts increased physical contact between stromal and tumor cells (22).…”
Section: Saa3 Ablation Alters the Transcriptional Profile Of Cafs Andmentioning
confidence: 79%
“…GSEA pathway analysis of Saa3-null CAFs revealed a significant enrichment in Proliferation and Angiogenesis hallmarks, as well as up-regulation of Sonic Hedgehog, TNFα/NFκB, and IL-6 pathways. Moreover, we observed enrichment in genes implicated in EMT, suggesting increased plasticity of Saa3-null CAFs as well as their potential effect in inducing an undifferentiated phenotype in their neighboring tumor cells (39). In addition, the Saa3-null CAFs displayed upregulation of the apical junction pathway, a property that predicts increased physical contact between stromal and tumor cells (22).…”
Section: Saa3 Ablation Alters the Transcriptional Profile Of Cafs Andmentioning
confidence: 79%
“…Accumulating evidence has demonstrated that EMT, a process including gene expression modifications that allow concurrent epithelial phenotype repression and mesenchymal phenotype activation, is an early event in the distant metastasis of tumor cells. 32 , 33 In addition, the hallmarks and regulators of EMT, such as E-cadherin, N-cadherin, SNAIL family proteins, TWIST1/2, and ZEB1/2, can be detected in human eCCA specimens, and their presence has been correlated with poor prognosis. 26 , 34 To explore whether MSI2 promoted the invasion and metastasis of eCCA cells by inducing EMT, we detected EMT-related markers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the tumour microenvironment resident fibroblasts, pericytes and bone marrow-derived mesenchymal cells, endothelial cells via EndMT or epithelial tumour cells can undergo an EMT process and become CAFs [ 101 , 102 ]. There have been a few reports proving the epithelial origin of CAFs: breast cancer cells from a patient biopsy have been characterized in vitro and have been found to co-express low levels of keratins together with high levels of α-SMA and these cells also exhibited a fibroblast-like morphology [ 103 ].…”
Section: Cancer-associated Fibroblasts (Cafs): Their Origin and LImentioning
confidence: 99%